The Utility of Routine Histopathological Examination of the Appendectomy Specimens - Hasan, Abdulkarim; Nafie, Khalid Mohamed; Abbadi, Osama Sharafeldin; Ibrahim, Adel Abdelwahid (Annals of Pathology and Laboratory Medicine, 2020)
Background: Appendectomy is the most commonly performed surgical procedure worldwide to manage appendicitis. The practice of sending all appendices specimens for routine histopathology examination depends on the concerned clinician. This study was performed to reveal the importance of routine histopathology examination of the appendectomy specimens with recording of the occurrence and distribution of unusual pathologic findings Methods: This was a retrospective record based comparative study performed in a single Hospital in Saudi Arabia, where the medical files of 766 patients were recruited. The appendectomy specimens were obtained either from our hospital or referred from any other hospital for histopathology examination. All the unusual diagnoses were reviewed by the histopathology author and blindly re-evaluated by other pathology consultant. Statistic analysis was performed manually. Result: 700 cases were within the usual histopathology scope. Unusual histopathological findings were observed in 66 cases (8.6%): four cases of mucinous neoplasms, 20 cases of fibrous obliteration or appendiceal neuroma, 18 cases showed parasitic infestation, and 24 cases were periappendicitis without appendicular acute inflammation. Conclusion: Routine histopathology examination of the appendix not only confirms the clinical diagnosis of acute appendicitis, but also leads to the incidental diagnosis of much unusual pathologies which could have been missed by the surgeon, and these pathologies include parasitic infestation, peri-appendicitis, neuromas and appendiceal mucinous neoplasms.